Active monitoring improves radiopharmaceutical administration quality - Crowley, James R.; Barvi, Iryna; Kiser, Jackson W. (Frontiers in Nuclear Medicine, 2023)
Introduction In 2016, our center adopted technology to routinely monitor 18F-FDG radiopharmaceutical administrations. Within six months of following basic quality improvement methodology, our technologists reduced extravasation rates from 13.3% to 2.9% (p < 0.0001). These same technologists administer other radiopharmaceuticals (without monitoring technology) for general nuclear medicine procedures in a separate facility at the clinic. Our hypothesis was that they would apply 18F-FDG lessons-learned to 99mTc-MDP administrations and that 99mTc-MDP manual injection extravasation rate would be consistent with the ongoing 18F-FDG manual injection extravasation rate (3.4%). We tested our hypothesis by following the same quality improvement methodology and added monitoring equipment to measure extravasation rates for 99mTc-MDP administrations. Results 816 99mTc-MDP administrations were monitored during 16-month period (four 4-month periods: A, B, C, D). Period A (first four months of active monitoring) extravasation rate was not statistically different from the Measure Phase extravasation rate of the previously completed PET/CT QI Project: 12.75% compared to 13.3% (p-0.7925). Period A extravasation rate was statistically different from Period C (months 9–12) extravasation rate and Period D (months 13–16) extravasation rate: 12.75% compared to 2.94% and to 3.43% (p < 0.0001). During Period C and D technologists achieved extravasation rates comparable to the longstanding manual 18F-FDG injection extravasation rate (3.4%). Conclusion Our initial hypothesis, that awareness of a problem and the steps need to correct it would result in process improvement, was not accurate. While those factors are important, they are not sufficient. Our findings suggest that active monitoring and the associated display of results are critical to quality improvement efforts to reduce and sustain radiopharmaceutical extravasation rates.